Structure of the Parallel Duplex of Poly(A) RNA: Evaluation of a 50 Year‐Old Prediction1. Issue 39 (27th June 2013) - Safaee, Nozhat; Noronha, Anne M.; Rodionov, Dmitry; Kozlov, Guennadi; Wilds, Christopher J.; Sheldrick, George M.; Gehring, Kalle
<x xml:space="preserve">Abstract</x> The other double helix: The molecular structure of double‐stranded poly(rA) was predicted in 1961, but it has only now been confirmed. The crystal structure of the parallel double helix of (rA)11 obtained at physiological pH was solved using ab initio direct methods and refined to 1.0 Å resolution. The crystals have bound ammonium ions that are complexed by the RNA phosphates and adenine N1 atoms (see section of the structure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>